Verification of Performance in Results-Based Financing : The Case of Community and Demand-Side RBF in Rwanda - Renaud, Adrien; Semasaka, Jean-Paul (World Bank, Washington, DC, 2014)
Rwanda, led by its Ministry of Health, was the first African country to implement Performance- Based Financing (PBF) nationwide in its health centers and hospitals. The country then went on to pilot RBF interventions at the community level. Rewarding community members who provide and use Maternal and Child Health (MCH) services is an innovative form of Results-Based Financing (RBF). The supply-side of this community PBF scheme focuses on cooperatives of Community Health Workers (CHWs). It pays them to provide selected MCH services and rewards them for the quality of their reporting as well as for good management. Conversely, the demand-side of this community PBF scheme provides women with in-kind incentives when they utilize three selected MCH services in health centers. Verifying the performance of these interventions is an integral part of RBF program implementation. This case study aims to describe the verification mechanisms used in Rwanda, which include monthly verification of the quantity of services provided by the CHWs, quarterly assessment of the quality of the functioning of the CHW cooperatives (including its reporting), verification of the quantity of in-kind incentives distributed in a less systematic way, as well as counter-verification of these three verification processes. This paper presents results of these verification methods, and discusses the obstacles faced, the way they were addressed, and the challenges that are still ahead. This case study is part of a broader analysis, involving multiple country case examples. It endeavors to expand knowledge about verification processes and practices and to address the design and implementation needs of RBF programs.